Economic sociology in China: Past and promises - Ping Fu; Dian Yang (economic sociology. perspectives and conversations, 2021)
Chinese sociology has a long-standing tradition of studying economic phenomena. Although the academic research and discipline construction of contemporary Chinese economic sociology are directly affected by Western economic sociology after the 1970s, Chinese sociologists carried out a large amount of investigation and research on economic phenomena and economic problems before the founding of the People's Republic of China (PRC) in 1949. The social surveys carried out by scholars record the transformation of Chinese traditional economic and social structure and bring forth a group of influential scholars and academic thought of far-reaching value. (...)
Keywords: 300